The real-time impact on real economy: A multivariate bvar analysis of digital payment systems and economic growth in India - Debasis Rooj; Reshmi Sengupta (Asian Development Bank Institute (ADBI), 2020)
Financial sector development can play a crucial role in driving economic growth. Innovation in the payment system can potentially impact output, prices, and monetary policy transmissions. However, there is a conspicuous lack of work on the role of the payment system in driving economic activity, especially for an emerging economy like India. This paper examines the dynamic linkage between a digital payment system, real-time gross settlement (RTGS), and economic growth in India, using a multivariate Bayesian vector autoregressive (BVAR) model. Using monthly observations on the value and the volume of RTGS, we show that the value of RTGS has a significant impact on both income and price level in the economy. Our results also indicate that both RTGS and economic growth positively and significantly impact each other, supporting the existence of bidirectional causality between the two. A variance decomposition analysis confirms that both RTGS and economic activity contribute significantly to each other's fluctuations. Several sensitivity analyses reinforce our main findings.
Keywords: E32; G22; C53; 330; financial innovation; RTGS; economic growth; bidirectional casualty; Bayesian vector autoregressive